Functioning in business - Knowless, P. Lance; Haukom, Richard; Glaser, Russ; Bailey, Francis project direction ([S.l.] : Longman ELT Video, 1989)
Focused on functioning a new business between the company in Japan and a company in America. Also described on how one company will function their business.
Adapted from the text Functioning in businesss by P. Lance Knowless and Francis Balley
Director of photography, Mark Boscacci ; cameraman, Ted Leyhe
Keywords: Business consultants -- Training of